Impact of breast reconstruction on the self-esteem of women after mastectomy for breast cancer (Research, Society and Development, 2023)
Introduction: It is understood that breast cancer is the result of the disordered increase of cells in the breast tissue, being considered a rare disease in young women, but its incidence increases with age, especially after the age of 50. Objectives: The primary objective of this research is to analyze the impact of breast surgery on perceptions of self-esteem, quality of life, health satisfaction, physical appearance, performance of daily activities and negative feelings of patients undergoing mastectomies as part of the breast cancer treatment. Methodology: The aim is to analyze the impact of breast augmentation surgery on the quality of life and emotional well-being of patients who have undergone mastectomy as part of breast cancer treatment. To this end, quantitative analysis research of a cross-sectional and retrospective nature was carried out. Results: In this study, a sample consisted of ten women with breast cancer. They were divided into two groups for a more specific analysis: Group 01, which included three women with breast cancer in the pre-surgical mastectomy stage. Conclusion: In this study, it was possible to understand that breast supervision, despite the complexities inherent to the entire process, provides quality of life and contentment to patients in almost all aspects that were applied. The importance of offering breast surgery as part of breast cancer treatment was highlighted, not only to improve self-esteem, but also to promote emotional and physical well-being and quality of life.